Perancangan Sistem Informasi Manajemen pada Ternak Ikan Lele di Jakarta - Nathania Rachel Lumban Batu; Najwa Aulia; Ardaffa Ihsan Sulus; Zatin Niqotaini (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
This study designs an inventory management information system for a catfish farm to replace inaccurate manual recording. Using a qualitative method based on observation and literature review, the system requirements were analyzed to overcome operational constraints regarding feed stock, seeds, and production yields. The database design was carried out through ERD, CDM, and PDM models that integrate data on farmers, ponds, catfish seeds, feed, feeding activities, and harvests. This system is intended for pond operators for daily operations, and farm owners for report oversight. The results of this design are expected to create a more digital, transparent, and efficient inventory management for catfish farming business owners